Analisis Perbedaan Jumlah Penumpang Kereta Api Pada Bulan Yang Memiliki Hari Libur Terbanyak Dan Paling Sedikit Di Stasiun Purwokerto Tahun 2023 - Tripena, Agustini; Amru, Diwyacitta (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
In general train passengers refer to individuals who use train transportation services to travel between cities or regions. In addition to daily travel, trains are also an option when there are national holidays such as Eid al-Fitr, Christmas, and New Year. The number of train passengers tends to surge when the holiday season arrives. Therefore, this study aims to analyze the difference in the number of train passengers in the month with the highest and least number of holidays at Purwokerto Station during 2023. The methods used in this study include descriptive statistics, normality test, and independent sample t-test. Passenger count data was collected every month throughout 2023, then analyzed to identify the months with the most and least holidays. Descriptive statistics were used to provide an overview of the distribution of passenger numbers. A normality test was conducted to check whether the ridership data was normally distributed. Furthermore, an independent sample t-test was used to determine if there was a significant difference in the number of passengers between the months with the most and least holidays. The results showe that there is a significant difference in the number of train passengers between the two categories of months. This is obtained from the results of the independent sample t-test, the sig. value is <0.01, whose value is <0.05 and the Sig. (2-tailed) of 0.476 whose value is> 0.05.